Preoperative sentinel lymph node identification, biopsy and localisation using contrast enhanced ultrasound (CEUS) in patients with breast cancer: a systematic review and meta-analysis. Issue 11 (November 2017) - Nielsen Moody, A.; Bull, J.; Culpan, A.-M.; Munyombwe, T.; Sharma, N.; Whitaker, M.; Wolstenhulme, S.
Abstract : Aim: To evaluate whether contrast-enhanced ultrasound (CEUS)-guided core biopsy of the sentinel lymph node (SLN) could identify metastatic nodes preoperatively and reduce the number of surgical SLN biopsies in patients with breast cancer and normal axillary B-mode ultrasound; and to establish whether CEUS SLN identification and localisation is a viable alternative to standard lymphatic mapping using isotope and blue dye. Materials and methods: A search of several electronic databases was performed and identified studies were assessed using QUADAS-2 for methodological quality. Pooled estimates of sensitivity and specificity for identification of nodal metastases were calculated. Results: Eleven prospective studies and one retrospective study with 1, 520 participants were included. The SLN identification and localisation rate for CEUS-guided skin marking was 70–100%, CEUS guided-wire localisation was 89–97%, and CEUS-guided iodine-125 ( 125 I) seed localisation was 60%. Across the four studies that evaluated preoperative CEUS-guided SLN biopsy, pooled sensitivity for identification of nodal metastases was 54% (95% confidence interval [CI]: 47–61) and pooled specificity 100% (95% CI: 99–100). Conclusion: CEUS is a promising technique for preoperative staging of the axilla. CEUS-guided core biopsy has the potential to identify nodal metastases in over half (54%) of patients with normal axillary B-mode ultrasound. CEUS-guided identification and localisation of the SLN may offer a viable alternative to standard lymphatic mapping using isotope and blue dye; however, further prospective studies with larger samples are warranted.